2021
DOI: 10.2147/cmar.s321324
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Nomogram for Predicting Recurrence-Free Survival of Surgical Resected Retroperitoneal Liposarcoma

Abstract: Background and Objectives: Surgical treatment is still the mainstay of curative therapy for retroperitoneal liposarcoma (RLPS), but often recurs after surgical resection. We aimed to establish a nomogram for postoperative recurrence of RLPS based on the Asian population. Methods: Patients after surgical resection at the South Hospital of Zhongshan Hospital/ Shanghai Public Health Clinical Center between August 2011 and December 2020 were included. The enrolled patients are randomly divided into training set an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Also interesting is the finding that tumor size is an independent risk factor for CSS, not for OS. The 5-cm threshold used in the AJCC staging system is still limited about the value for RPLs because such small RPLs are uncommon in the present and other international studies ( 17 , 25 , 35 , 43 ). Meanwhile, several studies proposed that the optimal threshold in tumor sizes should be revised upward to 10 cm ( 25 , 36 ).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Also interesting is the finding that tumor size is an independent risk factor for CSS, not for OS. The 5-cm threshold used in the AJCC staging system is still limited about the value for RPLs because such small RPLs are uncommon in the present and other international studies ( 17 , 25 , 35 , 43 ). Meanwhile, several studies proposed that the optimal threshold in tumor sizes should be revised upward to 10 cm ( 25 , 36 ).…”
Section: Discussionmentioning
confidence: 73%
“…Additionally, we found that patients with a distant and regional SEER stage had poor OS and CSS than those with a localized SEER stage. As the other authors suggested, patients with tumors invading adjacent structures may be more likely to develop residual microscopic or gross disease after resection ( 17 , 31 , 41 , 44 ). In this study, histological subtype was also an important indicator of prognosis.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In addition to stage, additional known prognostic factors include patient age at presentation, histologic subtype, complete resection with negative margins and without intra-operative tumor rupture, and provision of care at a specialized sarcoma center is associated with better outcomes. Therefore, various staging systems, nomograms and predictive tools have been devised [ 58 , 59 , 60 , 61 ].…”
Section: Staging and Nomogramsmentioning
confidence: 99%